Menelisik Empat Pilar Capital Kehidupan pada Ritual Adat Pa’ol Sau Suku Buna’ - Tes, Novinalis Emandus; Tahu, Guerikus Irwandi; Umbu Zerri, Mario Venerial; Kono, Vincentius De Paulo; Subani, Yohanes (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Technological advances are very attractive to millennials, so ancient things such as customs or culture are ignored. Pa'ol Sao is also one of the cultures that tend to be ignored, so the values contained in it are unknown. The purpose of this research is to reveal the meaning and value of life in the Pa'ol Sao ritual. The method used is descriptive, with an ontological theoretical reference as the basis for solving the existing problems. It was found that the Buna' people live under the auspices of four capitals, namely: material, intellectual, social, and spiritual. The four capitals become the main pillars that create harmony of life through their respective roles. The results of this research can become knowledge that, if understood properly, can also become a practice of living together in harmony and peace